Mengembangkan Budaya Penelitian Berintegritas - Kurniawati Martha; Yonathan Winardi; Pingkan Imelda Wuisan (Sekolah Tinggi Theologia Nazarene Indonesia, 2023)
Methods in educational research in UPH Teachers College is a course that prepares Teachers College students to be thinkers, researchers, and competent writers based on a biblical Christian worldview. The gap the researchers came across was a need for this course to be integrated with the biblical Christian worldview to develop research with integrity. The researchers then designed a module that was used in methodology class, and the method used is a descriptive qualitative, involving 110 students from 4 majors who took this course in the odd semester of 2021. This research's purpose is to elaborate on the usage of this module which is significant in helping the students to comprehend the biblical Christian worldview. The research results show that 96.36% of the students stated that the module equipped them to have a biblical Christian worldview for doing research. The results of the usage of modules show that students can conduct research based on a Christian worldview with integrity. Things for future improvement are the feedback and motivational words, attention to the layout by providing a navigation feature, and fun learning concepts using formal, popular, and communicative Indonesian language. A two-way dialogue style can make the module more interactive and an addition to learning videos made by the lecturers.